Fact searching in investigative reporting in Indonesia: a case study of Tempo and Gatra magazines - Kurnia, Septiawan Santana; Siti Suriani Othman; Firmansyah; Kuswarno, Engkus (Penerbit Universiti Kebangsaan Malaysia, 2020)
Investigative journalism is a new development in the Indonesian press and the study is at infancy. However, news magazines have investigated quite a number of scandals and problems in Indonesia during the Reformation era, post-New Order authoritarian regimes. This research examines fact searching activities at two main news magazines in Indonesia namely Tempo and Gatra in the process of producing investigative stories. This study deploys case study and an in-depth interview in its exploration of identifying specific processes involved in the process of producing investigative stories in these two news organizations. The interview was conducted with six informants including journalists at Tempo and Gatra news magazine, book authors and journalism analysts. The results of the study indicate that news magazines in Indonesia reveal various issues and cases, which are deliberately hidden to the community. The findings also demonstrate that the facts searching process encompasses several styles that effectively complement each other in news narration, especially with the particular concept, attitude, direction and effort to report its best to the society. This suggests that investigative stories in Indonesia news magazines emphasize the originality of news with in-depth coverage based on independent position, free from the influence of other societal entities, government’s pressure, as well as from other interests.